What students tell teachers about practices that integrate subjects with english in a lower secondary school in Portugal - Piacentini, Valentina (2018)
CLIL (Content and Language Integrated Learning) is an approach thought to provide, mainly during Content (non-language, subject) classes, a meaningful environment at school for the use and learning of a foreign language (FL), and may also improve conditions and practices of the specific subject. Moreover, CLIL can represent a research context to gauge the importance of language-aware teaching as is the case with the Portuguese “English Plus” project (EP), in which History and Science are taught/ learnt with/in English at lower secondary school. Our doctoral research is designed as a descriptive-explanatory case study on the EP project and its participants (English and Science teachers, former and current students). More specifically, this work focuses on students and shows their relationship with the EP approach and (dis)advantages in learning a subject with a FL. Data were collected through a semi-structured questionnaire and interview, with subsequent content analysis. The importance of “integrated learning” and of diverse strategies used by the teacher to support/scaffold learning is present in students’ perspectives which may further influence teaching practices.